KEABSAHAN SERTIFIKAT JAMINAN HAK TANGGUNGAN ELEKTRONIK SEBAGAI PELUNASAN KREDIT BERMASALAH - Nasution, Ariqah (Universitas Harapan Medan, 2023)
One form of collateral regulated under statutory regulations is a mortgage guarantee right where the object is a movable object based on UUPA number 60 of 1960. Currently, due to developments in science and technology, previously conventional mortgage guarantee certificates have changed to electronic guarantee certificates. mortgage right which is shortened to el certificate. The problem is what is the validity of the electronic mortgage guarantee certificate as collateral for non-performing loans? The research method used in this research is normative legal research or research which is synonymous with library research which is by developments in society. The validity of the electronic mortgage guarantee certificate as evidence for non-performing loans has the same legal force as manual mortgage rights, where the mortgage rights have the same force as a court decision in the event of problematic credit or the debtor defaults. Collateral objects registered based on electronic mortgage rights can be executed as debt repayment to the debtor. This is by the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 9 of 2019 concerning Electronic Integrated Mortgage Services, the ITE Law, and several other regulations relating to the validity of electronic documents.